Penerapan Metode Ajar Joyful Learning untuk Meningkatkan Motivasi Belajar Alkitab Siswa - Hani Rohayani; Jemima Angelica Tivani Winarto (Sekolah Tinggi Teologi Sriwijaya, 2025)
This study aims to investigate the effect of implementing the joyful learning method on improving the motivation to learn the Bible among students at Syalom Kindergarten in West Jakarta. The scope of the research is limited to 25 students and be conducted from January to May of the 2025/2026 academic year. The method used is descriptive qualitative within the framework of collaborative Classroom Action Research (CAR) over 2 cycles. Data collection was carried out with observation using a motivation observation sheet, daily anecdotal records, semi-structured teacher interviews, and documentation, with motivation indicators including activity, attention, participation, and recall response. Qualitative results are presented descriptively and are reinforced by descriptive quantitative data in the form of motivation score percentages. The percentage is calculated using the formula (total motivation score obtained ÷ total maximum score) × 100%, which representing the proportion of motivation achievement relative to the ideal score. The success of the intervention is determined when motivation reaches ≥85% (very well-developed category). In Cycle I, joyful learning were implemented using an expressive storytelling strategy over three meetings. The results showed 70.59% with 20 out of 25 students categorized as motivated, but the class was still generally passive and unfocused. In Cycle II, joyful learning was integrated with puzzle games to make learning more interactive; the achievement increased to 94.12% with 24 out of 25 students motivated, and the students appeared more active and enthusiastic, although one child still had difficulty following the activities.